Rethinking technology innovation for mental health: framework for multi-sectoral collaboration - Suh, Jina; Pendse, Sachin R.; Lewis, Robert; Howe, Esther; Saha, Koustuv; Okoli, Ebele; Amores, Judith; Ramos, Gonzalo; Shen, Jenny; Borghouts, Judith; Sharma, Ashish; Pedrelli, Paola; et al. (Nature Mental Health, 2024)
The impact of technology on mental health has become a core concern for researchers and practitioners from the clinical science, public health and technology sectors. One factor that influences this impact is the large gap between the silos of technologies explicitly designed as mental health support tools and the everyday technologies that inadvertently affect mental health. Here we ground our position on findings from a workshop that brought together over 60 experts and emphasize the importance of a multi-sectoral collaboration across these silos to address the complexities of technology’s impact on mental health. Our specific recommendations include a push to align stakeholders, incentives and governance, adopting person-centered and proactive mental health evaluation, and empowering users and clinicians (and their interactions) through mental health and technology literacy. We highlight sector-specific adaptations that can support greater collaborations, toward a future in which users have consistently positive interactions between technology use and their mental health.